2020
DOI: 10.3389/fped.2020.00329
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Dexmedetomidine on Emergence Agitation or Delirium in Children After Anesthesia—A Systematic Review and Meta-Analysis of Clinical Studies

Abstract: Background: We conducted this systematic review and meta-analysis to investigate the clinical effect of dexmedetomidine in preventing pediatric emergence agitation (EA) or delirium (ED) following anesthesia compared with placebo or other sedatives. Methods: The databases of Pubmed, Embase, and Cochrane Library were searched until 8th January 2020. Inclusion criteria were participants with age<18 years and studies of comparison between dexmedetomidine and placebo or other sedatives. Exclusion criteria included … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
38
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 102 publications
(272 reference statements)
1
38
1
1
Order By: Relevance
“…Our meta-analysis suggested that DEX was superior to midazolam for preventing EA in children, in line with the findings of Lang et al (89) and Rao et al (13). TSA and GRADE results revealed that the level of evidence about the DEX's superiority over midazolam in reducing EA incidence was sufficient.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Our meta-analysis suggested that DEX was superior to midazolam for preventing EA in children, in line with the findings of Lang et al (89) and Rao et al (13). TSA and GRADE results revealed that the level of evidence about the DEX's superiority over midazolam in reducing EA incidence was sufficient.…”
Section: Discussionsupporting
confidence: 88%
“…The preventive effect of DEX on EA in children has been documented in several meta-analyses (7)(8)(9)(10)(11)(12)(13). Although four relevant meta-analyses (7-10) published during 2014-2015 seemed to confirm the superiority of DEX on EA in children, the limited number of included studies reduced the reliability of outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The correlation between the face, legs, activity, cry, consolability (FLACC) score, duration of anesthesia, and history of previous operation and both Watcha score and pediatric anesthesia emergence delirium (PAED) score. review and metaanalysis support the superiority of dexm edetomidine over placebo, midazolam, or opioid in significantly decreasing the incidence of ED in pediatrics aft er anesthesia for various types of surgeries [23]. The same evidence was also confirmed in a network analysis of ped iatric anesthesia for adenotonsillectomy operation [24].…”
Section: Discussionmentioning
confidence: 86%
“…A study by Jun-Li Cao et al stated that objective pain score was lower in dexmedetomidine group at 15, 30, and 45minutes [18] . A study by Yuquan Rao et al stated that compared with placebo, midazolam, and opioids, dexmedetomidine significantly decreased the incidence of post-anesthesia emergence agitation or delirium in pediatric patients [19] . A meta-analysis by Juan Ni et al stated that dexmedetomidine decreased the incidence of severe pain (p<0.001) and need of rescue drug (p<0.001).…”
Section: Discussionmentioning
confidence: 99%